Mathematical modeling of oscillating water column wave energy converter devices over the undulated sea bed. (August 2020) - Koley, Santanu; Trivedi, Kshma
Abstract: The present study deals with the hydrodynamic performance of an OWC (oscillating water column) wave energy converter device placed on an undulated bed. The bed undulation is finitely extended and beyond that, the water bed is uniform in nature. The mathematical problem is studied in the two-dimensional Cartesian coordinate system under the linearized water wave theory. To solve the associated boundary value problem, a coupled eigenfunction expansion - boundary element method is used. The numerical convergence of the coupled eigenfunction expansion - boundary element method is provided. The effects of the width of the OWC device chamber, front wall submergence depth and inclination with the vertical axis, and the bed undulations on the hydrodynamic efficiency of the OWC device is discussed in detail.